Ventilation efficacy during paediatric cardiopulmonary resuscitation (PEDIVENT): simulation-based comparative study - Skrisovska, Tamara; Djakow, Jana; Jabandziev, Petr; Kramplova, Tereza; Klucka, Jozef; Kosinova, Martina; Stourac, Petr (Frontiers in Medicine, 2024)
Introduction: This simulation-based study aims to evaluate the efficacy of ventilation during paediatric cardiopulmonary resuscitation (CPR) provided by health care professionals (HCPs) and lay rescuers (LR). The objective is to assess the number of effective breaths delivered during the initial sequence of CPR. Effective ventilation plays a critical role during paediatric CPR, as most cardiac arrests are secondary to hypoxia in origin. The recommendations on initial resuscitation in unresponsive, non-breathing children differ worldwide. The European Resuscitation Council (ERC) guidelines recommend five breaths before starting the chest compressions. Yet, this recommendation was based on the expert consensus historically and has not changed since 2000 because of the lack of evidence. This research addresses the identified knowledge gap, with potential implications for improving resuscitation practices and ultimately enhancing patient outcomes. Methods: HCPs and LRs performed 90 seconds of CPR involving two mannequins: 5 kg Baby and 20 kg Junior. Both groups (HCPs and LRs) performed the task before and after structured CPR training, and the efficacy of ventilation before and after the training was compared. The HCPs provided bag-mask ventilation; LR performed dispatcher-assisted CPR with mouth-to-mouth ventilation. Results: The number of participants that reached the primary outcome before and after the training in Baby was in HCPs 26 (65%) vs 40 (100%) and in LRs 28 (60.9%) vs45(97.8%), (improvement in both P˂0.001). In the Junior mannequin, the primary outcome was reached by 31 HCP (77.5%) before and 32 HCP (82.1%) after the training (P=0.77) in the LR group 32 (82.1%) vs. 37 LR (94.9%), P=0.005. Discussion: This simulation-based study is the first to investigate ventilation efficacy during paediatric CPR provided by HCPs and LRs.Ventilation represents an important aspect of good-quality CPR in children. The concept of initiating paediatric CPR with initial breaths, as stated in ERC guidelines 2021, is justifiable. Trained HCPs and LRs providing dispatcherassisted CPR could deliver effective ventilation to paediatric mannequins. These findings can contribute to future research in this area, and address identified knowledge gaps concerning resuscitation guidelines, given the unique practical application of simulation as a research tool. 1.